Relocation and Resettlement - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on approaches to relocation and resettlement of people. Although resettlement is ideally avoided, the complexities of unclear, unrecognized, informal, and overlapping land claims in many areas means that it is an issue that investors and governments often need to address. Field research suggests room for improvement in processes and outcomes where resettlement had been undertaken. Critical factors for success included how resettled people perceived that their living situations had changed after resettlement, which includes compensation, access to livelihood opportunities, and social services. Also important was the extent to which people were consulted, where involved in decision making, and had access to grievance mechanisms.